THE RELATIONSHIP BETWEEN CONSUMER DOUBT AND VALUE FOR MONEY ON PURCHASE INTENTION - Hareka, Janice Ardelia; Wahyudi, Alexander (International Business Management - Universitas Ciputra, 2020)
This research is done to find out the relationship between consumer doubt and value for money on purchase intention. This research uses quantitative method by collecting data through questionnaires of 30 respondents, sample is done by purposive random sampling method. In this research, analysis of relationship was done between consumer doubt, and value for money on purchase intention to find out which variables affects purchase intention. What distinguishes this research from other researches is that there is a new product that has been owned yet by the more well-known brand of smartphones, namely the existence of the back screen that is used to take self- photographs by using the rear camera. Hypothesis is done to produces calculation statistics that the factor of purchase intention, that is consumer doubt affecting negatively on purchase intention, and value for money affecting positively on purchase intention.